Description of the Yield State of Bioplastics on Examples of Starch-Based Plastics and PLA/PBAT Blends - Teresa FRAS; Masahiro NISHIDA; Alexis RUSINEK; Ryszard Bolesław PĘCHERSKI; Norio FUKUDA (Engineering Transactions, 2014)
The present work concerns the description of the yield state of biodegradable materials. As examples, biodegradable polymers are chosen – cornpole CRP-M2, starch fatty acid ester, and PLA/PBAT, poly(lactic acid) (PLA) blended with poly(butylene adipate/terephthalate) (PBAT), [1-2]. These biodegradable, plant-derived bioplastics are a promising alternative to petroleum-based plastics. To describe the onset of plasticity in the bioplastics under discussion, Burzyński ´s hypothesis of material effort has been applied, [3-4]. The applied criteria account for the differential strength effect and for the shear correction resulting from the difference between experimental and theoretical values obtained as a result of the Huber-Mises approach, [5-6]. In general, these properties of yield state are characteristic for polymers. The description of yield state for bioplastics is an issue that has hardly been investigated, where illustrates the novel nature of this paper in which this topic is discussed.